A new species and a new record of Pyxine (Physciaceae) with norstictic acid from São Paulo State, Brazil - Jungbluth, Patricia [UNESP]; Marcelli, Marcelo Pinto; Kalb, Klaus (Mycotaxon Ltd, 2011)
In the course of a study of Pyxine species in São Paulo State, Brazil, Pyxine jolyana was recognized as a new species. It has norstictic acid in the medulla, a rare feature in South American species. Also, another species with norstictic acid, P. fallax, is recorded for the first time from the Neotropics. A world key to the Pyxine species that produce norstictic acid is presented.
Keywords: Pyxine albovirens; P. patellaris; P. retirugella var. capitata; P. retirugella; lichenized fungi